In Vitro Models of Tissue and Organ Regeneration (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The recovery of cells after tissue and organ injury is a complex process, more detailed insights into the cellular processes of repair and regeneration are urgently needed if we are to understand underlying molecular biological mechanisms. Based on this knowledge, this Special Issue will focus on current in vitro systems exploring repair and regeneration mechanisms. As such, this SI includes experimental research approaches to investigate the mechanisms involved and laboratory methods to establish and optimise models for tissue and organ repair and regeneration, theoretical modelling and computational models, as well as review papers are included here. Eleven articles are published in the Special Issue, which deals with various tissue and organ regeneration questions or the modelling or summary of the research models used in this process.